Synthesis, Structure Activity Relationships and Biological Activity Evaluation of Novel Spirocyclic Thiazolidin-4-ones as Potential Anti-Breast Cancer and Epidermal Growth Factor Receptor Inhibitors - Fleita, D. H.; Sakka, O. K.; Mohareb, R. M. (Drug Research, 2014)
A series of triazaspiro[4.5]dec-8-ene benzylidine derivatives containing thiazolidinone ring system (6–18) have been designed, synthesized and their biological activities evaluated as potential epidermal growth factor receptor inhibitors. Among them, 9-amino-2-(4-nitrobenzylidene)-3-oxo-4-phenyl-7-thioxo-1-thia-4,6,8-triazaspiro[4.5]dec-8-ene-10-carbonitrile (18) displayed the most potent inhibitory activity (IC50=6.355 µM). Antiproliferative assay results indicated that compound 18 exhibited moderate antiproliferative activity against MCF-7 cell line in vitro; with GI50 value of 30.6 µM. In addition, compounds 7 and 15 displayed the highest antiproliferative activity at a common GI50 value of 10.8 µM. Docking simulation was performed to determine the probable binding model and to pursuit information regarding the activity of compound 18. Based on the preliminary results, compound 18 could be used as an attractive building block for designing potential epidermal growth factor receptor inhibitors.
Keywords: spiro-thiazolidin-4-one; EGFR; antiproliferative; structure activity relationship